The Counselling Interview Proficiency Scale: The Progressive Development of a Scale for the Evaluation of Specific Counselling Interview Competencies - Klas, L. D. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article describes the development and suggested application of a scale which the writer developed for the evaluation of individual counselling interview competencies. The scale, called the Counselling Interview Proficiency Scale, can beused by the counsellor himself or by an independent rater and can be applied to liveor taped interviews. The scale is viewed by the writer as being in the process of refinement and those trying the scale are encouraged to provide feedback on the scaleto the writer. In addition, the reader is encouraged to define and validate competencies not appearing on this scale but felt to be crucial in the reader'scounselling setting.